Early Imperial Handmade South Gaulish Pottery from Lower Germany - Liesen, Bernd (Rei Cretariae Romanae Fautorum Acta, 2015)
Excavations in Lower Germany have unearthed a small group of early Imperial, handmade pots of South Gaulish origin (types Haltern 94/95; Gellep 449 and Hofheim 122; Tongeren 109; Deru P59). In Southern Gaul most of those forms occur both as wheelmade and handmade versions. Many of the handmade vessels show traces of additional treatment on a slow-turning wheel. This article aims to describe the type range and the fabrics of this group. Some aspects of their import into Germany are also discussed here.